Inhibitory power of young coconut fiber ethanol extract (Cocos nucifera Linn) on the growth of Bacteria staphylococcus aureus and Escherichia coli in tofu. Issue 1 (January 2021) - Sumarni, N K; Rahmawati,; Ruslan,
Abstract: Analysis of the growth of bacteria Staphylococcus aureus and Escherichia coli has been carried out on tofu that is soaked in ethanol extract of coconut coir (Cocos nucifera Linn). This study aims to determine the lowest total growth of the bacteria Staphylococcus aureus and Escherichia coli in tofu that is immersed in ethanol extract of young coconut fibre-based on variation in concentration a storage time. Young coconut coir is extracted using 96% ethanol and applied in various concentrations from 1000 to 7000 ppm with a soaking time of 24, 48, 72, and 96-hour, respectively. The total bacteria in the tofu from each treatment was calculated by the total plate count method. Based on the results obtained, it can be seen that the lowest total growth of Staphylococcus aureus is 3751 CFU/g, which is immersed at a concentration of 7000 ppm for 24-hour. As for the Escherichia coli bacteria as much as 4737 CFU/g, which was soaked at the same concentration for 96-hour.